Figure 8 in Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy - Bianucci, Giovanni; Landini, Walter (Zenodo, 2006)
Figure 8. Zygophyseter varolai gen. et sp. nov. Teeth of the holotype (MAUL 229/1). A, reconstruction of the original orientation of two isolated maxillary teeth; B, three mandibular teeth in place showing the gingival collar and the occlusal wear of the roots; C, D, two isolated maxillary teeth (arrows show the wear due to the opposite teeth). Published as part of Bianucci, Giovanni & Landini, Walter, 2006, Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy, pp. 103-131 in Zoological Journal of the Linnean Society 148 (1) on page 114, DOI:10.1111/j.1096-3642.2006.00228.x, http://zenodo.org/record/5427349